2015
DOI: 10.1093/ecco-jcc/jjv187
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Thiopurine or Anti-TNF Initiation Is Associated with the Risk of Major Abdominal Surgery in Crohn’s Disease: A Retrospective Cohort Study

Abstract: In our experience, time between diagnosis and thiopurine or anti-TNF initiation was associated with the risk of major abdominal surgery in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…However within this cohort referral patterns to the Southampton paediatric IBD referral centre have not changed over the study period, routine use of faecal calprotectin in children was not introduced to the region until 2016‐2017 and we have not observed a reduction in the disease severity at diagnosis . Additionally, data recently published do not indicate a general shift to earlier diagnosis or improved diagnostics in children with IBD, with significant diagnostic delay remaining common in recent years . These data suggest that the increased time from diagnosis to surgery is not accounted for by improved diagnosis.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However within this cohort referral patterns to the Southampton paediatric IBD referral centre have not changed over the study period, routine use of faecal calprotectin in children was not introduced to the region until 2016‐2017 and we have not observed a reduction in the disease severity at diagnosis . Additionally, data recently published do not indicate a general shift to earlier diagnosis or improved diagnostics in children with IBD, with significant diagnostic delay remaining common in recent years . These data suggest that the increased time from diagnosis to surgery is not accounted for by improved diagnosis.…”
Section: Discussionmentioning
confidence: 54%
“…31 Additionally, data recently published do not indicate a general shift to earlier diagnosis or improved diagnostics in children with IBD, with significant diagnostic delay remaining common in recent years. 32,33 41,42 There is a trend towards top-down medicine when treating IBD in adult populations, with early initiation of anti-TNF therapy aiming to modify disease course. 43 Whilst this is not yet recommended in paediatric practice, the promise of reducing surgical resection rates with prompt initiation of anti-TNF therapy is one of the reasons leading to increased use.…”
Section: Survival Analysismentioning
confidence: 99%
“…However, this study considered patients with both ulcerative colitis (UC) and CD together in a single category despite the fact that these two diseases can manifest quite differently. A Spanish study revealed that time between diagnosis and anti-TNF initiation was associated with the risk of major abdominal surgery in CD [16]. More specifically, out of 272 patients who received anti-TNF therapy, 137 patients who had undergone surgery started anti-TNF agents after a median of 166 months (IQR, 90 to 233) after diagnosis, while patients who had not undergone surgery started therapy after a median of 59 months (IQR, 14 to 162; p < 0,005) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that independent risk factors associated with SR were penetrating disease behavior, ileocolonic disease location, and isolated upper GI disease location. However, the use of TPs was an independent protective factor of SR. Several studies indicated that TPs could prevent and reduce the incidence of the first intestinal resection of CD patients . A meta‐analysis including 17 retrospective observational studies demonstrated that the use of TPs could reduce the risk of first bowel resection by 40% in CD patients .…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of TPs was an independent protective factor of SR. Several studies indicated that TPs could prevent and reduce the incidence of the first intestinal resection of CD patients. 21,22 A meta-analysis including 17 retrospective observational studies demonstrated that the use of TPs could reduce the risk of first bowel resection by 40% in CD patients. 23 However, few studies focused on the effect of postoperative TPs therapy on SR as the primary outcome among CD patients.…”
Section: Discussionmentioning
confidence: 99%